Development of a polymerase chain reaction method for diagnosis of Babesia ovis infection in sheep and goats - Aktas, M; Altay, K; Dumanli, N (Elsevier Science Bv, 2005)
In this study, a pair of oligonucleotide primers were designed according to the nucleotide sequence of the small subunit ribosomal RNA (ssu rRNA) gene of Babesia ovis isolated from sheep in eastern Turkey. The primers were used to detect parasite DNA from blood samples of B. ovis-infected sheep and goats by polymerase chain reaction (PCR). A 549-bp DNA fragment was specifically amplified from blood samples from sheep and goats, naturally infected with B. ovis. No PCR products resulted from Babesia motasi, T ovis, Theileria sp. OT1, Theileria sp. OT3, T lestoquardi, B. canis, B. microti, T annulata or normal sheep leucocytes DNA using these specific primers. B. ovis-infected erythrocytes with 1% parasitemia were subjected to 10-fold serial dilutions (from 10(-1) to 10(-9)) using an uninfected sheep erythrocytes, and DNA was extracted from each diluted sample for testing the sensitivity of the PCR. The PCR was sensitive enough to detect parasite DNA from the dilution of 10(-5) with 0.00001% parasitemia. This is more sensitive than examining 200 fields under light microscopy. In addition, 98 field samples collected from small ruminanats in eastern Turkey were tested for B. ovis infection. Four samples were positive Babesia spp. in blood smears, 21 samples were positive for B. ovis DNA by PCR. These results indicate that the PCR provides a useful diagnostic tool for the detection of B. ovis infection in sheep and goats. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Babesia ovis; sheep and goats; PCR; Microscopy; specific primers